'External timing' of placebo analgesia in an experimental model of sustained pain. (6th March 2021) - Camerone, Eleonora Maria; Wiech, Katja; Benedetti, Fabrizio; Carlino, Elisa; Job, Mirko; Scafoglieri, Aldo; Testa, Marco
Abstract: Background: Research on placebo analgesia commonly focuses on the impact of information about direction (i.e., increase or decrease of pain) and magnitude of the expected analgesic effect, whereas temporal aspects of expectations have received little attention so far. In a recent study, using short‐lasting, low‐intensity stimuli, we demonstrated that placebo analgesia onset is influenced by temporal information. Here, we investigate whether the same effect of temporal suggestions can be found in longer lasting, high‐intensity pain in a Cold Pressor Test (CPT). Methods: Fifty‐three healthy volunteers were allocated to one of three groups. Participants were informed that the application of an (inert‐)cream would reduce pain after 5 min (P5) or 30 min (P30). The third group was informed that the cream only had hydrating properties (NE). All participants completed the CPT at baseline and 10 (Test 10) and 35 min (Test 35) following cream application. Percentage change in exposure time (pain tolerance) from baseline to Test 10 (Δ10) and to Test 35 (Δ35) and changes in heart rate (HR) during CPT were compared between the three groups. Results: Δ10 was greater in P5 than in NE and P30, indicating that analgesia was only present in the group that was expecting an early onset of analgesia. Δ35 was greater in P5 and P30 compared to NE, reflecting a delayed onset of analgesia in P30 and maintained analgesia in P5. HR differences between groups were not significant. Conclusions: Our data suggest that 'externally timing' of placebo analgesia may be possible for prolonged types of pain. Significance: Research on placebo effects mainly focuses on the influence of information about direction (i.e., increase or decrease of pain) and magnitude (i.e., strong or weak) of the expected effect but ignores temporal aspects of expectations. In our study in healthy volunteers, the reported onset of placebo analgesia followed the temporal information provided. Such 'external timing' effects could not only aid the clinical use of placebo treatment (e.g., in open‐label placebos) but also support the efficacy of active drugs.